PERAN PENDIDIKAN KEWARGANEGARAAN DALAM UPAYA MENUMBUHKAN RASA CINTA TANAH AIR - Yudi Firmansyah (Universitas Buana Perjuangan Karawang, 2019)
The younger generation or the next generation is the generation that will start the results of the struggle of the predecessors by becoming leaders, who can support and advance this nation to become more prosperous and victorious. To make the young generation able to become good leaders who are expected to happen that do not need the love and self-defense of the State that grows in their hearts and souls. The feeling of love to the motherland is very important and must be instilled in the next generation of young people, so that in the future this nation can become a great and victorious nation. This research is a field research, with the type of qualitative descriptive research with the method used is a case study. Citizenship education in this study has an impact on the role of efforts to foster a sense of patriotism for students. The love of the motherland is a thank you and a love for the place of birth or homeland. Helping every successor generation to a large extent be able to apply a sense of love for the land by means of his beik through civic education. Keywords: Citizenship Education, Love the Motherland Generasi muda atau generasi penerus adalah generasi yang akan meneruskan hasil perjuangan para pendahulu dengan menjadi pemimpin-pemimpin, yang di harapkan dapat merubah dan memajukan bangsa ini menjadi lebih makmur dan berjaya. Untuk menjadikan generasi muda dapat menjadi pemimpin yang baik seperti yang di harapkan tidak akan terjadi apabila tidak rasa cinta dan bela Negara yang tumbuh di hati dan jiwa mereka. Rasa cinta kepada tanah air sangat penting dan harus di tanamkan kepada generasi muda penerus bangsa, agar kedepannya bangsa ini dapat menjadi bangsa yang besar dan Berjaya. Penelitian ini merupakan penelitian lapangan (field research), dengan jenis penelitian deskriptif kualitatif dengan metode yang digunakan yaitu studi kasus. Pendidikan kewarganegaarn dalam penelitian ini mengarhkan kepada peranan dalam upaya menumbuhkan rasa cinta tanah air kepada siswa. Cinta tanah air adalah suatu kasih sayang dan suatu rasa cinta terhadap tempat kelahiran atau tanah airnya. Sehingga setiap generasi penerus bangsa terutama para pelajar mampu untuk mengimplementasikan rasa cinta tanah air dengan sebaik-beiknya melalui pendidikan kewarganegaraan. Kata kunci : Pendidikan Kewarganegaraan, Cinta Tanah Air